Positively Selected Sites at HCMV gB Furin Processing Region and Their Effects in Cleavage Efficiency - Stangherlin, Lucas M.; de Paula, Felipe N.; Icimoto, Marcelo Y.; Ruiz, Leonardo G. P.; Nogueira, Maurício L.; Braz, Antônio S. K.; Juliano, Luiz; da Silva, Maria C. C. (Frontiers in Microbiology, 2017)
Human cytomegalovirus is a ubiquitous infectious agent that affects mainly immunosuppressed, fetuses and newborns. The virus has several polymorphic regions, in particular in the envelope glycoproteins. The UL55 gene encodes the glycoprotein B that has a variable region, containing a furin cleavage site and according to the variability different genotypes are characterized. Here we investigated variability and existence of selective pressure on the UL55 variable region containing the furin cleavage site in 213 clinical sequences from patients worldwide. We showed the ocurrence of positive selective pressure on gB codons 461 and 462, near the furin cleavage site. Cleavage analysis of synthesized peptides demonstrated that most mutations confer better cleavage by furin, suggesting that evolution is acting in order to increase the efficiency cleavage and supporting the hypothesis that gB processing is important in the host. We also demonstrated that peptides containing sequences, that characterize genotypes gB2 and 3, are differentially cleaved by furin. Our data demonstrate for the first time that variability in the cleavage site is related to degree of gB procesing by furin.